Republic of Korea : Financial Sector Assessment Program-Technical Note-Non-Financial Balance Sheet Vulnerabilities and Risks to Financial Stability. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2020)
Non-Financial Corporate Sector. Non-financial corporate leverage as share of GDP in Korea remains higher than peer countries but has remained stable since 2013 at around 100 percent of GDP. The stock of non-corporate debt has become slightly more resilient due to the deleveraging of non-conglomerate affiliated firms. Average firm performance has remained resilient for conglomerate-affiliated corporates but weakened for all other firms. As a result, despite the low interest rate environment, around one-quarter of total corporate debt (around 28 percent of GDP) is registered 'at-risk'. Banks balance sheets are at risk as over half of non-financial corporate debt-at-risk resides with SMEs; Stress tests show that (i) Korean firms which are more indebted, less profitable, smaller and have lower turnover are more likely to experience difficulties servicing their debt; (ii) corporate balance sheets are vulnerable to a sudden hike in interest rates, which combined with a profit shock, could double the amount of debt-at-risk held by non-SME firms and; (iii) exchange rate shocks appear manageable given low FX debt and natural FX hedges. Under a downside macro-financial stress test scenario, non-SME credit losses would total a touch over 2 percent of GDP. Bank stress tests suggest that the maximum cumulative bank losses from distressed SME loans in a stress scenario would total around 2 percent of GDP. Together, these losses would be broadly manageable for the financial system to absorb.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet